SATIS: providing information on appropriate technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
There are a number of nongovernmental organisations which aim to adapt and develop simple forms of technology on the basis of existing knowledge. SATIS, which stands for Socially Appropriate Technology International Information Services, is designed...